Part A - PD-1/PD-L1 blockade in cancer immunotherapy/ Part B - Evaluation of PD-1/PD-L1 immune checkpoint inhibitors in a luciferase-reporter cell-based assay - Peredo Aguilar, Maria Azucena (2023)
Part A: Molecules that downregulate the immune response are key during cancer treatment because they pose a mechanism to avoid immunotherapy, also called immune checkpoints. In that regard, the PD-1/PD-L1 pathway has been thoroughly studied to deepen our understanding of the function of these immune checkpoint molecules. This signalling pathway involves the interaction of programmed cell death (PD-1), which is a surface protein found mainly in T and B cells, and programmed cell death ligand 1 (PD-L1) found in antigen-presenting cells. However, there is clear evidence demonstrating the overexpression of PD-L1 in some cancer cells, and when this protein interacts with PD-1, it leads to T-cell inactivation and thus helps cancer cells escape clearance by the immune system. In this literature review, the knowledge around the components of the PD-1/PD-L1 pathway and how these mediate immune evasion in the tumour microenvironment will be summarized. Given the importance of this signalling pathway, the potential for developing cancer therapeutics targeting this biological process started to grow. The predominant PD-1/PD-L1 inhibitors in the market are monoclonal antibodies, but there are other peptides and non-peptide molecules in research that seem promising in terms of their effectiveness and produce few immune adverse effects. To test the activity of such inhibitors, an array of assays can be used to characterize the molecules in different contexts, from a physicochemical to a cellular and organ level. Despite the favourable results, not all patients respond to PD-1/PD-L1 inhibitors and the reason for that, although not fully understood, is still an ongoing challenge. Overall, the complexity of the immune regulation mediated by PD-1 and PD-L1 is not completely unveiled but is an active area of cancer immunotherapy research.